Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan di Badan Keuangan Pemerintah Daerah Provinsi Gorontalo - Rizki Karim; Amir Lukum; Nurharyati Panigoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The financial statements of regional governments play a crucial role in creating accountability for local governments. Therefore, high-quality regional financial statements are needed as they can serve as a reference for policy-making and have a high level of quality for their users. This research aims to determine the influence of human resource competence on the quality of financial statements. This research employs descriptive quantitative. The sampling technique employed is purposive sampling. This research uses primary data collected by distributing questionnaires to 40 respondents involved in statement management. The data analysis technique used is simple linear regression analysis. The results indicate that human resource competence has a positive and significant influence on the quality of financial statements at the Regional Financial Agency of Gorontalo Province.